Development and Feasibility Assessment of Virtual Reality-Based Relaxation Self-Training Program - Jeong, Hyu Seok; Oh, Jooyoung; Paik, Minjeong; Kim, Hyunji; Jang, Sooah; Kim, Beom Soo; Kim, Jae-Jin (Frontiers in Virtual Reality, 2022)
Diaphragmatic breathing and progressive muscle relaxation (PMR) are an effective way for relaxation training and anxiety control, but their use is not common to the general public. Today, as the need for non-face-to-face contact increases, virtual reality (VR)-based self-training is gaining attention in public health. This study aimed to evaluate the feasibility of the newly developed VR-based relaxation training program. Both diaphragmatic breathing and PMR can be trained without an assistant using this VR application in three steps: (1) learning in a virtual clinic, (2) review in a comfortable virtual environment, and (3) practice in outdoor virtual environments. Self-training is recommended on a 3-week schedule with a total of 4 to 6 trials per day for 4 days a week. Thirty-one healthy volunteers were divided into the VR (n=15) and worksheet (n=16) groups, and participated in self-training under similar conditions as much as possible. Multiple evaluations were performed before, during, and after self-training. The change rates of all psychological and psychophysiological measures before and after self-training did not significantly differ between the two groups. The levels of tension after breathing practices showed no group difference, whereas those after PMR practices were significantly lower in the VR group than in the worksheet group. In the VR group, trials of outdoor practices tended to induce a decrease of the tension level, particularly after outdoor breathing trials. The VR group gave a practicable score of 70 points or more, average 43.5, and average 180.3 for usability, cybersickness, and presence of this program, respectively. These results suggest that the VR-based relaxation self-training program can be used by healthy people as a means of relaxation. In the use of this program, diaphragmatic breathing may be used more easily, but the benefit of using VR is higher in PMR. These findings provide justification for a randomized controlled study of whether this program can be used for stress relief in the general population and, furthermore, treatment of patients with anxiety disorders.